1996
DOI: 10.5144/0256-4947.1996.471
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Malignant Lymphoma in Al-Qassim, Saudi Arabia: A Retrospective Study

Abstract: The incidence and clinical characteristics of malignant lymphomas (ML), the most common tumors encountered in the Middle East, vary in different regions. [1][2][3][4][5] This retrospective study analyzed histologically confirmed cases of malignant lymphoma seen in King Fahd Specialist Hospital (KFSH) during an eight-year period (01/01/87 to 31/12/94). The results were compared with data from other regions of the Kingdom and the Middle East. KFSH is a 570-bed regional referral hospital of Al-Qassim region and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
(10 reference statements)
4
3
1
Order By: Relevance
“…Carcinoma was the second most common finding in adults. This finding is in agreement with other studies [3,19].…”
Section: Discussionsupporting
confidence: 96%
“…Carcinoma was the second most common finding in adults. This finding is in agreement with other studies [3,19].…”
Section: Discussionsupporting
confidence: 96%
“…NHL was the most frequent common HM (37.8%) in this study, resembles finding in cancer registries of Sana [17], and most Asian countries like Saudi Arabia [18,20,34], Jordan [35], Korea [7] , and Morocco and other African countries [8,[24][25][26], while in United States, Australia, and Bangladesh, leukemia cases were the most frequent HM [6,22,32,36] . NHL was more common in men than in women with a male to female ratio of 1.7:1 and this was similar to a previous study in lymphomas in Hadhramout [37] and other studies in Saudi Arabia but less ratio (1.2:1) was found in Oman [21,38]. We observed that the median age of NHL was 44 years which was similar to studies done in Sana, Saudi Arabia, Oman, and Jordan [17,35,39].…”
Section: Discussionsupporting
confidence: 91%
“…Al-Qassim is an arid desert with patches of oasis which is located in the central region of Saudi Arabia, and it has a population of about one million. 19 There are about 120 primary health-care centers (PHC) in Al Qassim city. The 11 PHCs were selected based on how they apply the quality measures, volume, and location.…”
Section: Methodsmentioning
confidence: 99%